Faktor-Faktor Yang Mempengaruhi Minat Technopreneur Mahasiswa Di Era Teknologi Digital (Studi Kasus: Mahasiswa ITB Ahmad Dahlan) - Ambardi Ambardi; Helmi Chaidir (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2020)
Growing entrepreneurial or techno-entrepreneurial interest in college students is believed to be an alternative measure to reduce unemployment. Because students are expected to be young educated entrepreneurs who are able to start their own businesses, and are able to open jobs for others. The need for qualified technopreneurs to use technology as a business booster has also increased. This is marked by many new inventions or innovations created based on digital technology. Therefore, to meet these needs, it is necessary to be supported by higher education institutions that prepare students and graduates to be able to create new jobs, in addition to creating innovative, adaptive, competitive science as the main concept of competitiveness and national development in the industrial revolution era 4.0. The purpose of this study is to find out what factors influence student interest to become technopreneur. This research was conducted on the campus of the Ahmad Dahlan Institute of Technology and Business using a questionnaire method. Questionnaires are distributed directly to respondents so that they get a high rate of return. Distribution and collection of questionnaires were carried out throughout the ITB Ahmad Dahlan campus. From the distribution of questionnaires collected data of 310 students. The method of data analysis in this study uses multiple linear regression analysis, which also performed validity, reliability and classical assumption tests. Data processing in this study uses SPSS version 22. From the results of this study indicate that the factors that influence students' interest to become technopreneur are self-esteem, innovation, leadership, profit, and the environment. As for personal challenges, the desire to be a boss and flexibility do not affect the interest in becoming a technopreneur among students.